2016
DOI: 10.1111/jth.13180
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K antagonists' use and fracture risk: results from a systematic review and meta‐analysis: reply

Abstract: results of this meta-analysis and systematic review. As we pointed out previously, it would be more valuable if the investigators could provide a more accurate estimation of the results after considering this comment. Disclosure of Conflict of InterestsThe authors state that they have no conflict of interest. 3 Jakobsen JC, Wetterslev J, Winkel P, Lange T, Gluud C. Thresholds for statistical and clinical significance in systematic reviews with meta-analytic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There is also debate on the potential adverse effect of warfarin on the skeleton in adults [4], but it has been recently suggested that warfarin use does not cause fragility fractures, especially in the hip [5][6][7]. This suggestion would be supported by the latest meta-analysis [8], although further research could be required [9,10]; in longitudinal studies, use of vitamin K antagonists was associated with the increased incidence of total and hip fractures (risk ratio 1.09, 95 % confidence interval 1.01 to 1.18 and 1.17, 1.05 to 1.31, respectively), but this association was not confirmed in those used variables for matching between vitamin K antagonist and control groups (1.03, 0.90 to 1.18 and 1.13, 0.96 to 1.34) [8]. Furthermore, a recent population-based study reported that atrial fibrillation was linked to the increased risk of fractures that could be reversed by warfarin therapy [11].…”
Section: Dear Editormentioning
confidence: 93%
“…There is also debate on the potential adverse effect of warfarin on the skeleton in adults [4], but it has been recently suggested that warfarin use does not cause fragility fractures, especially in the hip [5][6][7]. This suggestion would be supported by the latest meta-analysis [8], although further research could be required [9,10]; in longitudinal studies, use of vitamin K antagonists was associated with the increased incidence of total and hip fractures (risk ratio 1.09, 95 % confidence interval 1.01 to 1.18 and 1.17, 1.05 to 1.31, respectively), but this association was not confirmed in those used variables for matching between vitamin K antagonist and control groups (1.03, 0.90 to 1.18 and 1.13, 0.96 to 1.34) [8]. Furthermore, a recent population-based study reported that atrial fibrillation was linked to the increased risk of fractures that could be reversed by warfarin therapy [11].…”
Section: Dear Editormentioning
confidence: 93%